2013
DOI: 10.2214/ajr.12.8980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraparenchymal Blood Patch on Rates of Pneumothorax and Pneumothorax Requiring Chest Tube Placement After Percutaneous Lung Biopsy

Abstract: The use of an autologous intraparenchymal blood patch significantly reduces the rate of pneumothorax requiring chest tube placement. It seems to be more beneficial when a 19-gauge guiding needle is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…Lang et al 18 demonstrated a similar statistically significant decrease in both pneumothorax and chest tube placement in a prospective study of 100 patients. Malone et al, 19 in a larger prospective trial including 242 patients, reached statistical significance in chest tube reduction and noted a nonstatistically significant decrease in the pneumothorax rate. These reductions are similar to that seen in evaluations of other sealants including gel foam, 9,10 fibrin glue, 13 biopsy plugs, 14,15 and normal saline.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lang et al 18 demonstrated a similar statistically significant decrease in both pneumothorax and chest tube placement in a prospective study of 100 patients. Malone et al, 19 in a larger prospective trial including 242 patients, reached statistical significance in chest tube reduction and noted a nonstatistically significant decrease in the pneumothorax rate. These reductions are similar to that seen in evaluations of other sealants including gel foam, 9,10 fibrin glue, 13 biopsy plugs, 14,15 and normal saline.…”
Section: Discussionmentioning
confidence: 94%
“…This was brought into question in 1988 when a large controlled trial showed no significant benefit of the procedure 16 and was corroborated by an additional controlled study in 1990. 17 More recent research has emerged re-suggesting the effectiveness of autologous clotted blood with 2 prospective, randomized trials, 1 in 2000 18 and 1 in 2013, 19 both of which showed a significant decrease in chest tube placement rates.…”
Section: Discussionmentioning
confidence: 99%
“…6 Finally, the study by Malone et al examined 242 patients undergoing percutaneous biopsy of the lung and determined that the rate of pneumothorax requiring chest tube placement was significantly reduced in the group with an intraparenchymal blood patch compared with the control. 7 This study was ultimately chosen for analysis because it was a prospective, randomized controlled trial, had the largest sample size, was the most recent, and was most applicable to our patient. The patient population in this study included mostly elderly patients, patients with and without a smoking history, and a fairly equal amount of men and women.…”
Section: Research Articlementioning
confidence: 99%
“…No patients were lost to follow-up. 7 Standard protocol for biopsy was used, including patient fasting, use of sedation, and holding anticoagulation medications. All biopsies were done with CT guidance.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 1 more Smart Citation